SUMMARY ACCORDING SECURITY THREATS TO THE INTERNET OF THINGS - Norkuvvat Chunaev; Jakhongirbek Khabibullaev (TADQIQOTLAR, 2025)
Abstract: The concept of the Internet of Things (IoT) was introduced by Kevin Ashton at MIT in 1998. The vision of the concept is that objects, "things", are connected to each other and therefore create an IoT in which each object has its own individual identity and can interact with other objects. Internet of Things objects can vary greatly in size from small to the largest. The Internet of Things turns ordinary products such as cars, buildings and machines into smart devices, connected objects that can communicate with people, applications and each other. In the paper, we examine the prevalence of the Internet of Things in today’s world and its impact on various industries. The paper discusses the security threat of the Internet of Things and as a result, security recommendations will be made.